Crystal structure of trans-bis-thiocyanato-di(bis(pyrazolyl)methane)-copper(II), C16H16CuN10S2 - Van Langenberg K. A.; Murray K. S.; Tiekink E. R. T. (Zeitschrift für Kristallographie - New Crystal Structures, 2002)
C16H16CuN10S2, monoclinic, P121/c1 (No. 14), a = 8.670(1) Å,